Autochthonous West Nile virus infection in Germany: Increasing numbers and a rare encephalitis case in a kidney transplant recipient. Issue 2 (27th December 2021) - Schneider, Julia; Bachmann, Friederike; Choi, Mira; Kurvits, Lille; Schmidt, Marie Luisa; Bergfeld, Leon; Meier, Iris; Zuchowski, Marta; Werber, Dirk; Hofmann, Jörg; Ruprecht, Klemens; Eckardt, Kai‐Uwe; et al.
Abstract: West Nile Virus (WNV) infections are increasingly detected in birds and horses in central Europe, with the first mosquito‐borne autochthonous human infection detected in Germany in 2019. Human infections are typically asymptomatic, with occasional severe neurological disease. Because of a low number of cases in central Europe, awareness regarding potential cases is low and WNV diagnostic testing is not routine. We tested cerebrospinal fluid (CSF) samples from unsolved encephalitis and meningitis cases from Berlin from 2019 to 2020, and describe a WNV‐encephalitis case in a 33‐year‐old kidney transplant recipient. The infectious course was resolved by serology, RT‐PCR and sequencing of stored samples. Phylogenetic sequence analysis revealed a close relationship of the patient's WNV strain to German sequences from 2019 and 2020. A lack of travel history and patient self‐isolation during the SARS‐CoV‐2 pandemic suggest the infection was acquired in the patient's home or garden. Serological tests of four people sharing the living space were negative. Retrospective RT‐PCR and WNV‐IgM testing of 671 CSF samples from unsolved encephalitis and meningitis cases from Berlin detected no additional infections. The recent increase of WNV cases illustrates the importance of considering WNV in cases of meningoencephalitis, especially in immunocompromised patients, as described here. Proper education and communication and a revised diagnostic strategy will help to raise awareness and to detect future WNV infections.